The Relationship Between Learning Strategy for Office Aplication With Learning Succes at LKP Widyaloka Bukittinggi - Elinur Sakiyah; Vevi Sunarti (Universitas Negeri Padang, 2020)
This research was motivated by the low learning success in the office application training at LKP Widyaloka Bukittinggi. Researchers suspect that the cause of the training participants' low learning success is to the lack of implementation of learning strategies by the instructors. The problems studied in this research are,